An influence of fire upon the soil microbiocoenosis state of lea lands of not enough and long standing - Малиновская, И. М. (Scientific Progress & Innovations, 2012)
The study of the postpyrogenous and background plot state of light- and twenty-year lea lands has been shown that an influence of fire occurs on different mechanisms every three and fourteen months after its passing. The general processes that take place on account of fire after three months are following: a decrease of the amount of microorganisms, their physiological and biochemical activity, the carbon and nitrogen compound migration intensification with the exception of humus, an increase of soil phytotoxicity. After fourteen months the mentioned tendencies remain apart, from humus decay activity and phytotoxicity- they are reduced.